Anticipation of the Androgynous Mind in "El caballero de las botas azules" - Stratan, Sebastian (Madrygal. Revista de Estudios Gallegos, 2015)
The myth of the androgynous, similar to all archetypal representations of human existence, has been employed to justify different aspirations. Among its multiple avatars, in the 20th century it comes to justify the need for a conscious freedom from the chains of gender. Virginia Woolf was the first writer to coin the term in the name of the feminist movement. However, half a century before, in Galicia, Rosalía de Castro wrote a novel where she contemplates the theory of the narrative voice devoid of gender characteristics. Thus, the present article claims to demonstrate the manner in which El caballero de las botas azules anticipates what is generally attributed to Virginia Woolf.